Wind generator - Mohd Fazry, Mahpar (2010)
Wind is the one of the source of electricity distributed generation technology. Nowadays around entire worldwide can produce power by Alternating Current (AC) generator that is a common practice thus the implementation of wind generator. Sea breezes and land breezes can be important factors in a location's prevailing winds. At UMP campus Kuala Pahang it the one strategy places to generate the wind generator because it is near the sea. The advantages to use wind generator is environmental friendly refers than portable generator. As practically, wind generator doesn’t use any raw material. But, portable generator uses the fuel or petrol to generate the electricity. On the other hand, by using wind generator we will cut cost during running the system compare to the portable generator. In wind generator system, the output will be producing 120Watt to directly use to consumer. The system will be controlled by PIC microcontroller that controls the input signal (120Watt) directly to user. However, when the input signal is not produce 120Watt, the PIC microcontroller will give the signal to battery backup to user. Other than that, the battery will be inverting the source from Direct Current (DC) to Alternating Current (AC) before transfer to user